Effects of soil amendments on metal uptake, antioxidant activities and production of bioactive compounds by sunflower sprouts - Jittawan Kubola,; Theeraphan Chumroenphat,; Pichtel, John; Weeradej Meeinkuirt, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The effects of soil amendments on Cd and Zn uptake, bioactive compounds and antioxidant activities in two cultivars (Pacific 33 and Black Oil) of Helianthus annuus L. were evaluated. Dicalcium phosphate/cattle manure and leonardite/cattle manure mixed in a 1:1 w/w ratio with soil served as soil treatments. The Black Oil cultivar experienced greater metal uptake, biomass production and survival rate compared to the Pacific 33 cultivar. The increased Cd and Zn uptake (>0.2 and >99.4 mg/kg, respectively) in Black Oil cultivar exceeded the regulatory standard for vegetables. Significantly higher levels of bioactive compounds and antioxidant activities were detected in the control treatment for Pacific 33 leaves compared to Black Oil cultivar. Synergistic effects of heavy metals, amendment application and plant genotype are considered key factors in decreased levels of bioactive compounds and antioxidant activities.